1993
DOI: 10.1007/bf01316889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of naturally occurring glycoprotein C-negative herpes simplex virus type 1

Abstract: We previously isolated glycoprotein C (gC)-negative herpes simplex virus type 1 (HSV-1) mutants, TN-1, TN-2 and TN-3, from a patient with recurrent herpetic keratitis at one-year intervals. In the present study, the molecular basis for the inability of these clinical isolates to express gC was examined. The nucleotide sequence of the gC gene of the TN-1 strain was compared with that of the HSV-1 KOS strain. In the open reading frame of the gC gene, there were 12 nucleotide differences between the TN-1 and KOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…TN-1 exhibits a gC-negative phe notype, that is TN-1 virions and infected cells do not express gC on theirsurface. Toh et al [10] revealed that the mutation in the TN-1 gC gene resulted in a premature termination of gC translation and that the truncated gC produced in TN-1-infected cells were secreted into the extracellular fluid be cause o f the lack of the transmembrane domain. This secre tion of the truncated gC may be partly responsible for the induction of HSK in TN-l-inoculated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TN-1 exhibits a gC-negative phe notype, that is TN-1 virions and infected cells do not express gC on theirsurface. Toh et al [10] revealed that the mutation in the TN-1 gC gene resulted in a premature termination of gC translation and that the truncated gC produced in TN-1-infected cells were secreted into the extracellular fluid be cause o f the lack of the transmembrane domain. This secre tion of the truncated gC may be partly responsible for the induction of HSK in TN-l-inoculated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The truncated gC of TN-1 retains [10] one of the two pre viously designated major antigenic regions of gC [14], Fur thermore, BALB/c mice inoculated with TN-1 subcutane ously produced the antibody against the truncated gC [Minagawa, unpubl. data].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that DTH response was depressed in mice inoculated via the ic route with TN-1 differed from the findings of Hendricks et al [9] who reported that a gC-negative mutant HSV-1 g C -39 induced tolerance to cytotoxic responses but not to DTH. One possible explanation for this difference is that the truncated gC secreted by TN-1 infected cells [29] worked as the immunosuppressive antigen, in contrast to g C -39 which is totally defective in gC expression due to the deletion of the entire gC coding sequence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Since the isolation of a series of gC-deficient HSV-1 (TN-1, TN-2, TN-3) from a herpetic stromal keratitis patient (15), reports on the nature of TN-1 have been published by this laboratory (10,16,17,26,32). TN-1infected Vero cells secreted truncated gC resulting from an amber mutation at amino acid position 280 in the UL44 gene (32) out of 511 amino acids in the whole open reading frame.…”
mentioning
confidence: 99%
“…Since the isolation of a series of gC-deficient HSV-1 (TN-1, TN-2, TN-3) from a herpetic stromal keratitis patient (15), reports on the nature of TN-1 have been published by this laboratory (10,16,17,26,32). TN-1infected Vero cells secreted truncated gC resulting from an amber mutation at amino acid position 280 in the UL44 gene (32) out of 511 amino acids in the whole open reading frame. Structural studies of HSV-1 gC from other laboratories have located multiple antigenic sites with different biological activities in the gC glycoprotein (12,19,37): gC acts as a complement component C3b receptor (4) primarily within antigenic site I; the site which interacts with cell surface heparan sulfate was localized within antigenic site II.…”
mentioning
confidence: 99%